2014
DOI: 10.3389/fncel.2014.00174
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic strategies aimed at stimulating the endogenous production of allopregnanolone

Abstract: A growing number of studies indicate that 3-alpha reduced neurosteroids are remarkable analgesics in various pain states. This is the case for allopregnanolone (AP), one of the most potent endogenous positive allosteric modulators of GABAA receptor function. From the pioneering work of Hans Selye, who described the sedative properties of steroids, synthetic compounds resembling the progesterone metabolite AP have been developed. If some of them have been used as anesthetics, it seems difficult to propose them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Neurosteroids are steroidal hormones that are synthesized in the brain, and exert inhibitory effects mainly via GABA A receptors, glycine, and L-and T-type calcium channels [145][146][147][248][249][250][251]. Among the most common neurosteroids are progesterone, pregnanolone, and allopregnanolone.…”
Section: Neurosteroidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neurosteroids are steroidal hormones that are synthesized in the brain, and exert inhibitory effects mainly via GABA A receptors, glycine, and L-and T-type calcium channels [145][146][147][248][249][250][251]. Among the most common neurosteroids are progesterone, pregnanolone, and allopregnanolone.…”
Section: Neurosteroidsmentioning
confidence: 99%
“…Studies have revealed neurosteroids to have a therapeutic role in a number of conditions such as epilepsy, drug withdrawal-induced seizures, anxiety, premenstrual syndrome, stress, depression, and alcohol withdrawal. Furthermore, it is possible that some neurosteroids are produced in the nervous system in response to injury, exerting anti-inflammatory effects at the site of insult [145,251]. Of particular relevance to pain and opioid research is neurosteroids' role in modulating neuronal plasticity and related activities of the nervous system, as well as their role in the sexual dimorphism of pain processing [145].…”
Section: Neurosteroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a much faster pathway that alters ion channel activity through steroid activation of membrane receptors. Nongenomic signaling of the steroid hormone progesterone (P4) occurs on a time scale of seconds and is required for distinct physiological events, such as oocyte maturation (3) and human sperm cell activation (4, 5), and P4 likely triggers anesthesia in rodents (6). Many tissues have both nuclear and membrane progesterone receptors, which complicates identification of the latter.…”
mentioning
confidence: 99%